PHARMACOGNOSTIC STUDIES ON FLOWERS OF DREGEA VOLUBILIS: EVALUATION FOR AUTHENTICATION AND STANDARDIZATION - BHASKAR DAS; ARNAB DE; PIU DAS; AMALESH NANDA; AMALESH SAMANTA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The various parts of Dregea volubilis (Family: Apocynaceae), locally known as Jukti (Bengali), are commonly used in Indian system of medicine to treat various ailments such as inflammation, piles, leukoderma, asthma, and tumors. Literature review suggested that there has been no detailed work on systemic pharmacognostic and phytochemical studies done on the flowers of the plant. The present study is aimed to lay down quality control parameters for D. volubilis flowers to confirm its identity, quality, and purity. Methods: The present work was designed to study detailed organoleptic, histological, quantitative standards, physicochemical, spectroscopic, and chromatographic characteristics of the flowers of D. volubilis. Results: The total ash, acid insoluble ash, water soluble ash, loss on drying, water, and alcohol soluble extractive values were found to be 11.767±0.130% (w/w), 1.287±0.106% (w/w), 9.140±0.344% (w/w), 14.110±0.061% (w/w), 21.600±0.133% (w/v), and 9.603±0.104% (w/v), respectively. Phytochemical screening of different extracts showed the presence of carbohydrates, proteins, amino acids, steroids, glycosides, alkaloids, flavonoids, tannins, and phenolics. The chromatographic study revealed the presence of rhamnose (103.229±4.994 μg/g), fructose (738.670±25.714 μg/g), glucose (285.532±24.465 μg/g), and maltose (49.082±5.206 μg/g). Conclusion: The characterization parameters of the present study may serve as a reference standard for proper authentication, identification and for distinguishing the plant from its adulterants.